Ответ:
а)
б)9х²–(х–1)²= (3х–(х–1))(3х+(х–1))= (2х+1)(4х–1)
в) х³+(у^6)= (х+у²)(х²–ху²+у⁴)
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
а)![100{a}^{4} - \frac{1}{9} {b}^{2} = (10 {a}^{2} - \frac{1}{3} b) \times (10 {a}^{2} + \frac{1}{3} b) 100{a}^{4} - \frac{1}{9} {b}^{2} = (10 {a}^{2} - \frac{1}{3} b) \times (10 {a}^{2} + \frac{1}{3} b)](https://tex.z-dn.net/?f=100%7Ba%7D%5E%7B4%7D%20%20-%20%20%5Cfrac%7B1%7D%7B9%7D%20%7Bb%7D%5E%7B2%7D%20%20%3D%20%2810%20%7Ba%7D%5E%7B2%7D%20%20-%20%20%5Cfrac%7B1%7D%7B3%7D%20b%29%20%20%5Ctimes%20%2810%20%7Ba%7D%5E%7B2%7D%20%20%2B%20%20%5Cfrac%7B1%7D%7B3%7D%20b%29)
б)9х²–(х–1)²= (3х–(х–1))(3х+(х–1))= (2х+1)(4х–1)
в) х³+(у^6)= (х+у²)(х²–ху²+у⁴)